Assessment of Heavy and Toxic Metals in the Blood and Hair of Saudi Arabia Smokers Using Modern Analytical Techniques - Majed Alrobaian; Hassan Arida (International Journal of Analytical Chemistry)
Epidemiological studies on the heavy and toxic metal content in the human blood and hair of some smokers from Saudi Arabia were carried out by modern analytical techniques. The levels of some selected heavy and toxic metals (e.g.; Hg, Pb, Cd, As, Se, Mn, Zn, Ni, and Cr) were determined using inductively coupled plasma-atomic emission spectrometer (ICP-AES). Prior to the analysis, the blood and hair samples of Saudi Arabia smokers were collected, treated, and digested by microwave digestion system. The number of cigarettes per day as well as the smoking period was taken in consideration in this study. The tested elements concentrations in the investigated smoker blood and hair samples were compared with those obtained from some nonsmoking control samples. The samples were collected from the psychiatric hospital in Taif city after issuing the ethical committee license in this regard. The results obtained from this study represent a very important guide for the antismoking organizations. The assessment of some side effects of the smoking in such studies presents vital challenge for the social antismoking authorities and the stakeholder governments to attain the sustainable investment for their people.